2016
DOI: 10.3390/f7020038
|View full text |Cite
|
Sign up to set email alerts
|

Above- and Belowground Biomass Models for Trees in the Miombo Woodlands of Malawi

Abstract: Abstract:In this study we present general (multiple tree species from several sites) above-and belowground biomass models for trees in the miombo woodlands of Malawi. Such models are currently lacking in the country. The modelling was based on 74 trees comprising 33 different species with diameters at breast height (dbh) and total tree height (ht) ranging from 5.3 to 2 cm and from 3.0 to 25.0 m, respectively. Trees were collected from four silvicultural zones covering a wide range of conditions. We tested diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 36 publications
5
45
1
Order By: Relevance
“…The RS-ratio varied significantly between dbh classes with a high RS-ratio for small trees and lower RS-ratios for larger trees (Table 3). A similar pattern for miombo woodland trees was observed by [22] who found that the RS-ratio was decreasing significantly and non-linearly with increasing dbh. The use of RS-ratio is recommended for estimating belowground biomass in cases where models are not available [23] and mean RS-ratios are frequently applied to estimate belowground biomass [24].…”
Section: Discussionsupporting
confidence: 84%
“…The RS-ratio varied significantly between dbh classes with a high RS-ratio for small trees and lower RS-ratios for larger trees (Table 3). A similar pattern for miombo woodland trees was observed by [22] who found that the RS-ratio was decreasing significantly and non-linearly with increasing dbh. The use of RS-ratio is recommended for estimating belowground biomass in cases where models are not available [23] and mean RS-ratios are frequently applied to estimate belowground biomass [24].…”
Section: Discussionsupporting
confidence: 84%
“…This strongly indicates that the species allocates more biomass to root in colder sites, namely, the root-shoot ratio increases latitudinally [37]. In addition, the root-shoot ratio is an important factor for estimating belowground biomass when biomass models are not available [38].…”
Section: Discussionmentioning
confidence: 99%
“…For each tree in respective sample plots, we calculated biomass by using a model developed by Kachamba, et al [47] with dbh and ht as independent variables: Before calculating biomass, we predicted the ht of trees whose heights were not measured in the respective sample plots using a height-diameter model developed from the sample trees from all sample plots:…”
Section: Sampling Design and Ground Reference Data Collectionmentioning
confidence: 99%